PERAN LAYANAN BIMBINGAN KELOMPOK TEKNIK BEHAVIORISTIK DALAM MENINGKATKAN RASA PERCAYA DIRI PADA SISWA KELAS VIII MTs NEGERI 2 SURAKARTA TAHUN PELAJARAN 2021/2022 - Erwanto, Kurniawan Ade (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
Abstract: The purpose of this study is to investigate the effect of behavioristic technique group guidance services in building self-confidence in Class VIII students at MTs Negeri 2 Surakarta during the academic year 2021/2022. This research was conducted at MTs Negeri 2 Surakarta. The subjects in this study were students of class VIII. This research approach is qualitative research. Collecting research data using documentation techniques, interview techniques and observation techniques. The data analysis technique used was comparative descriptive analysis, which was to compare self-confidence between qualitatives. Based on the results of the research that the role of behavioristic technique group guidance services can increase the self-confidence of class VIII MTs Negeri 2 Surakarta students in the 2021/2022 academic year, self-confidence before being given guidance on benavioistic technique groups, it appears that students are still selfish, self-centered, students naturally excessive need for support from others, being pessimistic and less cheerful, worried about himself in front of others, and students are not confident in their abilities. After being given group guidance, students have better self-confidence which is shown by students being no longer selfish and able to work together with their friends, without needing excessive support from other people, students can be independent, optimistic and happy, confident in themselves in front of them, others, and students believe in their abilities. There are still two students whose self-confidence has not been maximized, this is understandable because there are several factors that affect self-confidence, including: Internal factors, including: student self-concept, student's physical condition, personal experience, education possessed, while external, including: the condition of parents, school environment, and peer association. Judging from the confidence of the two students through the behavioristic technique group guidance showed a significant increase. Key Words: behavioristic technique group guidance, increasing students' self-confidence.